2018
DOI: 10.1002/jcb.27583
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA small nucleolar RNA host gene 5 regulates trophoblast cell proliferation, invasion, and migration via modulating miR‐26a‐5p/N‐cadherin axis

Abstract: Pre-eclampsia (PE) is a pregnancy-specific disease characterized by the occurrence of hypertension and proteinuria after two weeks of gestation. Long noncoding RNAs (lncRNAs) are emerging as key regulators in PE development.This study aims to investigate the role of lncRNA, small nucleolar RNA host gene 5 (SNHG5), in the pathogenesis of PE. The expression of SNHG5 was significantly downregulated in placental tissues from patients with severe PE compared normal controls. Overexpression of SNHG5 promoted trophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…In addition to that, lncRNA‐ATB was manifested to be associated with the incidence of PE by means of the manipulation of the procedure of the cell invasion, coupled with the development of the endothelial vessels [51]. The decline in small nucleolar RNA host gene 5 (SNHG5) in the placentas of PE women indicated that SNHG5 induced not only cell proliferation, but also cell invasion, and migration through the manipulation of the miR‐26a‐5p/N‐cadherin axis [52]. The expression of lncRNA maternally expressed gene 3 (MEG3) in PE placentas was decreased as well [53].…”
Section: Lncrnas Affect Cellular Functions Of Trophoblast Cellsmentioning
confidence: 99%
“…In addition to that, lncRNA‐ATB was manifested to be associated with the incidence of PE by means of the manipulation of the procedure of the cell invasion, coupled with the development of the endothelial vessels [51]. The decline in small nucleolar RNA host gene 5 (SNHG5) in the placentas of PE women indicated that SNHG5 induced not only cell proliferation, but also cell invasion, and migration through the manipulation of the miR‐26a‐5p/N‐cadherin axis [52]. The expression of lncRNA maternally expressed gene 3 (MEG3) in PE placentas was decreased as well [53].…”
Section: Lncrnas Affect Cellular Functions Of Trophoblast Cellsmentioning
confidence: 99%
“…H19 inhibits the proliferation of trophoblast cells through encoding miR-675, which down-regulates the expression of NOMO1 54 . SNHG5 is known to promote cancer cell proliferation and survival 56 , and is recently reported to promote the proliferaction, invasion, and migration of trophoblast cells 57 . TUG1 is well documented to promote the proliferation, invasion, and colony formation of cancer cells 58 and trophoblast cells as well 59 .…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are capable of regulating the development and metabolism of several cellular activities at the epigenetic, transcriptional and post-transcriptional levels (30). A number of studies have shown that the abnormal expression of lncRNAs in placental tissues during pregnancy is closely related to the onset of pre-eclampsia (31,32). He et al (16) reported that 738 lncRNAs were differentially expressed in the placental tissues of patients with pre-eclampsia, including 479 that were upregulated and 259 that were downregulated.…”
Section: Discussionmentioning
confidence: 99%